The Appropriateness of English Materials Based on Teachers Lesson Plan on Multimedia Students at SMK Antartika 1 Sidoarjo - Anggia Dwinda Paramitha; Wahyu Taufiq (International Consortium of Education and Culture Research Studies, 2021)
The aimed of this study was to discover and analyzethe appropriateness of English learning material for the students based on teachers’ lesson plan. This study used qualitative method, the subject and object in this research is the document which is consisted of teaching materials in lesson plan on the first semester of tenth grade that the teacher used for teaching the students multimedia major at SMK Antartika 1 Sidoarjo. The data was collected by analze teachers’ lesson plan and interview. The result of this study showed that most of indicators about the appropriateness of teaching material for English specific purposes were not fulfilled and most of teaching material that teacher used was English for general purposes by follows the syllabus from department education. Hopefully, teachers could create appropriate teacjing materials and develop teaching material which appropriate English specific purposes for the students